2-[2-(4-Benzylpiperazin-1-ylcarbonyl)ethyl]-5,6-diphenylpyridazin-3(2H)-one - Aydin, Abdullah; Dogruer, Deniz S.; Akkurt, Mehmet; Büyükgüngör, Orhan (International Union of Crystallography (IUCr), 2008)
The title compound, C(30)H(30)N(4)O(2), has a non-planar conformation, the dihedral angles formed by the pyridazinone ring plane and the three phenyl rings being 54.61 (7), 51.10 (7) and 59.53 (8)°. The piperazine ring adopts a chair conformation. Inter- and intra-molecular C-H⋯O contacts are found in the crystal structure and these consolidate the three-dimensional packing.
Keywords: Organic Papers; 3. Good health